Spatial modeling of income inequality and population aging in Brazil (Research, Society and Development, 2021)
Objective: To analyze the spatial dynamics of income inequality and its relationship with population aging in Brazil. Method: A population-based ecological study using spatial analysis techniques and data from the last two Brazilian Demographic Census. Spatial modeling presented the Global Moran Index (I) and Local Spatial Association Index (LISA) through spatial autocorrelation, and the correlation between income inequality, life expectancy, and aging rate. Results: We observed significant spatial autocorrelation of income inequality (I=0.284, I=0.462; p=0.001), life expectancy (I=0.560, I=0.352; p=0.001), and aging rate (I=0.663, I=0.646; p=0.001). Predominant clusters were found in the North, Northeast, and Southern regions of the country. Clusters from the North and Northeast regions were associated with higher inequalities and lower indicators of aging. There was an inverse spatial correlation between income inequality, life expectancy, and aging rate. Conclusion: Population aging in Brazil presents a non-random distribution revealing spatial correlations with income inequality. Given the social and economic disparities across Brazilian territory, spatial analysis proved to be a significant contribution to the formulation of public policies that respect locoregional peculiarities.